DUAL A TEOLOGIJA PŘINOŠK K PROBLEMATICE WUŽIWANJA DUALOWYCH FORMOW W HORNJOSERBSKICH PŘEŁOŽKACH BIBLIJE - DZIKIEWICZ, DANIEL (Slavia Occidentalis, 2020)
This article describes the relations between dual grammatical number and theology. The original thesis was: Upper Sorbian translations of the Bible contain theologically problematic uses of dual forms. The hypothesis is accompanied by an analysis of the exegesis and theology of the periscopes Gen 1, 28; Mt 20, 23; £k 2, 7; J 1, 41 and 17, 21. Application or failure to apply dual forms in the texts in question poses significant problems on the level of theology. This article contains also a suggestion of certain rules to be followed in future revisions of the existing translation of the Upper Sorbian Bible. Firstly, the use of dual grammatical number should go hand in hand with the theological perspective of the biblical texts. Secondly, in cases when the category of dual grammatical number cannot accommodate theology, the latter should be a priority.